Successful cooling of a pixel tracker using gaseous helium: studies with a mock-up and a detector prototype - Rudzki, Thomas; Meier Aeschbacher, Frank; Deflorin, Marin; Flucher, Niculin (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2023)
We report the successful operation of a functional pixel detector with gaseous helium cooling. Using an accurate mock-up beforehand, the cooling was validated. We use a miniature turbo compressor to propel the helium at 2 g/s under ambient pressure conditions with gas temperatures above 0 °C. Our earlier results based on computational fluid dynamics simulations and a much simpler mock-up are confirmed. With this, we paved the path to cool pixel detectors in experimental particle physics at heat densities up to 400 mW/cm2 using helium. This enables cooling of detectors with very low mass requirements, minimising the effects of multiple Coulomb scattering effectively. This technique requires sensors tolerant to be operated in a wide temperature range and a detector geometry to guide the helium flow adequately. The concept presented here is not limited to pixel detector applications and can be used to cool any surface with comparable heat-densities, only limited by shaping the helium gas flow.